2021
DOI: 10.3390/polym13111855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cellulose and Cellulose Nanocrystal Contents on the Biodegradation, under Composting Conditions, of Hierarchical PLA Biocomposites

Abstract: In this work, the effect of microfibrillated cellulose (MFC) and cellulose nanocrystals (CNCs) on the biodegradation, under composting conditions, of hierarchical PLA biocomposites (HBCs) was studied using a full 22 factorial experimental design. The HBCs were prepared by extrusion processing and were composted for 180 days. At certain time intervals, the specimens were removed from the compost for their chemical, thermal and morphological characterizations. An ANOVA analysis was carried out at different compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
3
6
0
Order By: Relevance
“…It can be seen that the incorporation of cellulosic reinforcements decreases this fraction by up to 15%, with nanocrystals promoting this decrease to a greater extent. These results corroborate the crystallinity slow-down PLA biodegradation that other authors have pointed out [ 14 , 25 , 27 , 50 , 51 , 53 ]. Regarding the initial fraction that is most recalcitrant to biodegradation ( C s0 ), it can be seen that it ranges from 20 to 30% in the materials studied.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It can be seen that the incorporation of cellulosic reinforcements decreases this fraction by up to 15%, with nanocrystals promoting this decrease to a greater extent. These results corroborate the crystallinity slow-down PLA biodegradation that other authors have pointed out [ 14 , 25 , 27 , 50 , 51 , 53 ]. Regarding the initial fraction that is most recalcitrant to biodegradation ( C s0 ), it can be seen that it ranges from 20 to 30% in the materials studied.…”
Section: Resultssupporting
confidence: 92%
“…These results show that the NCCs, in presence of cellulose microfibers, enhance the biodegradability of PLA and are in agreement with the results reported by other authors [ 21 , 22 , 23 , 24 , 25 ]. Galera-Manzano et al [ 53 ] studied the drum-composting biodegradation of PLA multiscale composites and reported that a synergistic effect exists when both cellulosic fibers were incorporated simultaneously in the biocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the addition of microsized cellulose (MFC) significantly increased the weight loss and molecular weight loss of PLA during composting experiments, while the addition of CNC decreased both. This was explained by accelerated surface degradation in the presence of MFC, indicating that the biodegradation process started from the hydrophilic MFC . Opposite results have also been reported where the weight loss increased as a function of CNC addition to PHB/PCL blends .…”
Section: Degradation During Real or Simulated Compostingmentioning
confidence: 55%
“…This was explained by accelerated surface degradation in the presence of MFC, indicating that the biodegradation process started from the hydrophilic MFC. 103 Opposite results have also been reported where the weight loss increased as a function of CNC addition to PHB/ PCL blends. 104 In accordance, the blend of bacterial cellulose with PHB also increased the biodegradation of PHB as measured by the release of CO 2 under controlled aerobic composting conditions.…”
Section: Degradation During Real or Simulated Compostingmentioning
confidence: 99%
“…Other studies focused on the design factors affecting the speed and degree of degradation. For example, microfibrillated cellulose was found to increase the degradation of PLA composites while cellulose nanocrystals retard degradation ( Manzano et al ., 2021 ). The material thickness was also found to correlate with the disintegration speed of PLA and PBS blends ( Tolga et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%